2019
DOI: 10.1016/j.jcta.2019.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Hopf algebra structure of symmetric and quasisymmetric functions in superspace

Abstract: We show that the ring of symmetric functions in superspace is a cocommutative and self-dual Hopf algebra. We provide formulas for the action of the coproduct and the antipode on various bases of that ring. We introduce the ring sQSym of quasisymmetric functions in superspace and show that it is a Hopf algebra. We give explicitly the product, coproduct and antipode on the basis of monomial quasisymmetric functions in superspace. We prove that the Hopf dual of sQSym, the ring sNSym of noncommutative symmetric fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…. , 0) a composition of length r. The fermionic degree of F 1 r is exactly r. In [11], they show that a r,s exists and express it as a sum of ±1, but they do not give an explicit formula. Furthermore, they indicate that a r,s = (−1) rs a s,r .…”
Section: Quasisymmetric Invariants On the Exterior Algebramentioning
confidence: 99%
See 1 more Smart Citation
“…. , 0) a composition of length r. The fermionic degree of F 1 r is exactly r. In [11], they show that a r,s exists and express it as a sum of ±1, but they do not give an explicit formula. Furthermore, they indicate that a r,s = (−1) rs a s,r .…”
Section: Quasisymmetric Invariants On the Exterior Algebramentioning
confidence: 99%
“…Quasisymmetric functions generate a commutative subalgebra. In [11], the authors showed that the quasisymmetric functions in one set of commuting variables and one set of anticommuting variables forms a graded Hopf algebra. This implies that the quasisymmetric functions in one set of anticommuting variables are closed under multiplication and the space is spanned by one element at each non-negative degree.…”
Section: Quasisymmetric Invariants On the Exterior Algebramentioning
confidence: 99%
“…In [11], the authors showed that the quasisymmetric functions in one set of commuting variables and one set of anticommuting variables forms a graded Hopf algebra. This implies that the quasisymmetric functions in one set of anticommuting variables are closed under multiplication and the space is spanned by one element at each nonnegative degree.…”
Section: Quasisymmetric Functions Generate a Commutative Subalgebramentioning
confidence: 99%
“…In the notation of [11], where is a composition of length r . The “ ” over a part in [11] is to indicate a fermionic component. Therefore, the fermionic degree of is exactly r .…”
Section: Quasisymmetric Invariants On the Exterior Algebramentioning
confidence: 99%
See 1 more Smart Citation